2018
DOI: 10.3390/ijms19082418
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Causes Skeletal Muscle Atrophy and Modulates Muscle Chronometabolism

Abstract: Antibiotics lead to increased susceptibility to colonization by pathogenic organisms, with different effects on the host-microbiota relationship. Here, we show that metronidazole treatment of specific pathogen-free (SPF) mice results in a significant increase of the bacterial phylum Proteobacteria in fecal pellets. Furthermore, metronidazole in SPF mice decreases hind limb muscle weight and results in smaller fibers in the tibialis anterior muscle. In the gastrocnemius muscle, metronidazole causes upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 44 publications
(60 reference statements)
6
77
0
Order By: Relevance
“…These data agreed with Manickam et al's study, which demonstrated dysbiosis in pathogen-free mice treated with the antibiotic metronidazole producing scarce gastrocnemius muscle mass, abnormal activation of atrophy genes, and insulin resistence [209]. Conversely, fecal transplantation of old human subjects with high physical performance, called high functioning, in germ-free mice induced a peculiar microflora rich in Prevotella and Barnesiella species and developed more grip strength [210].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisesupporting
confidence: 90%
“…These data agreed with Manickam et al's study, which demonstrated dysbiosis in pathogen-free mice treated with the antibiotic metronidazole producing scarce gastrocnemius muscle mass, abnormal activation of atrophy genes, and insulin resistence [209]. Conversely, fecal transplantation of old human subjects with high physical performance, called high functioning, in germ-free mice induced a peculiar microflora rich in Prevotella and Barnesiella species and developed more grip strength [210].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisesupporting
confidence: 90%
“…In support of this, the muscle mass/body weight ratio was reduced in young GFM, and colonization of GFM with fecal samples from age-matched conventionally raised mice restored the muscle mass/body weight ratio (Lahiri et al, 2019). Similarly, in antibiotic-treated young mice, muscle mass was reduced (Manickam et al, 2018;Nay et al, 2019;Okamoto et al, 2019) without a corresponding change in body weight (Manickam et al, 2018;Okamoto et al, 2019), thereby resulting in a decreased muscle mass/body weight ratio (Nay et al, 2019). In addition, muscle mass and the muscle mass/body weight ratio were increased following natural microbiota seeding in antibiotic-treated mice (Nay et al, 2019).…”
Section: Role Of the Gut Microbiome And Short-chain Fatty Acids On Skmentioning
confidence: 70%
“…However, conventionalized mice treated with metronidazole, leading to Proteobacteria in mouse feces, perpetuated changes in the metabolic and circadian profiles of the gastrocnemius muscle. Expression of PPAR-g and its target gene adiponectin as well as circadian clock genes Per2, Cry2, Ror-b, and E4BP4 were all up-regulated in the skeletal muscle of the treated SPF mice but not in GF mice (242). How this impacts mice physiologically and metabolically is yet to be elucidated.…”
Section: Ppar the Gut Microbiota And Musclementioning
confidence: 96%
“…4). Conventionalized mice treated with metronidazole, a class of antimicrobial drug that targets anaerobic bacteria, demonstrated the significant impact of an altered gut microbiota on the skeletal muscle (242). Metronidazole treatment led to an increase in Proteobacteria in mouse feces.…”
Section: Ppar the Gut Microbiota And Musclementioning
confidence: 99%